CONSTITUITVE HOLDERS AND DEFINITION OF MINORITIES IN THE HUNGARIAN AND MACEDONIAN CASE (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The paper presents a comparative analysis of the legal regulations in the Republic of North Macedonia (Macedonia) and the Republic of Hungary related to state foundation, constitutive holders and definition of minorities. Considering that both countries have populations of different ethnic backgrounds, a comparison is made to examine how minorities issues are regulated and whether they are part of the state constitution.The comparative analysis reveals differences in terms of the history of state formation, constitutive documents and legal acts related to the protection of minorities. However, similarities exist in the utilization of the ethnic element in definition of constitutive holders.